Preliminary metabolomic analysis of goat milk from different breeds using mass spectrometry - Abd Rahman M.R.; Hassan Z.; Hassan M.S.; Hashim R.; Norlelawati Arifin; Mohd Nazmi Abd Manap (Insight Society, 2024)
Indexed by Scopus